2023
DOI: 10.1177/15330338231206003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of microRNAs in Regulating Cancer Cell Response to Oxaliplatin-Containing Regimens

Ali Tavakoli Pirzaman,
Manijeh Ebrahimzadeh Pirshahid,
Bahareh Babajani
et al.

Abstract: Oxaliplatin (cyclohexane-1,2-diamine; oxalate; platinum [2+]) is a third-generation chemotherapeutic drug with anticancer effects. Oxaliplatin has a role in the treatment of several cancers. It is one of the few drugs which can eliminate the neoplastic cells of colorectal cancer. Also, it has an influential role in breast cancer, lung cancer, bladder cancer, prostate cancer, and gastric cancer. Although oxaliplatin has many beneficial effects in cancer treatment, resistance to this drug is in the way to cure n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 156 publications
(211 reference statements)
0
1
0
Order By: Relevance
“…Drugs used to treat cancer can directly or indirectly damage DNA and interfere with it, causing chromosomal aberrations or strand breaks. [9][10][11][12] Research has shown that some chemotherapeutic drugs can also cross the blood-testis barrier, which can have negative effects on the testicles. These organs are sensitive to the toxic effects of chemotherapy, which can cause damage to germ cells or lead to and fibrosis of the interstitial tissue.…”
Section: Fu-induced Testicular Damagementioning
confidence: 99%
“…Drugs used to treat cancer can directly or indirectly damage DNA and interfere with it, causing chromosomal aberrations or strand breaks. [9][10][11][12] Research has shown that some chemotherapeutic drugs can also cross the blood-testis barrier, which can have negative effects on the testicles. These organs are sensitive to the toxic effects of chemotherapy, which can cause damage to germ cells or lead to and fibrosis of the interstitial tissue.…”
Section: Fu-induced Testicular Damagementioning
confidence: 99%